Low Cost and Secure Smart Meter Communications using the TV White Spaces - Fatemieh, Omid; Chandra, Ranveer; Gunter, Carl (IEEE International Symposium on Resilient Control Systems (ISRCS '10), 2010)
We investigate the use of white spaces in the TV spectrum for Advanced Meter Infrastructure (AMI) communications. We provide a design for using white spaces for AMI and show its benefits in terms of bandwidth, deployment, and cost. We also discuss ongoing work on applying machine learning classification techniques to improve the attack resilience of spectrum data fusion in the proposed architecture.